2021
DOI: 10.1590/0034-7167-2020-0275
|View full text |Cite
|
Sign up to set email alerts
|

Costs of healthcare-associated infections in an Intensive Care Unit

Abstract: Objectives: to evaluate hospitalization costs of patients with and without Healthcare-Associated Infections an Intensive Care Unit. Methods: a retrospective case-control study. Data collection was retrieved from the medical records of Intensive Care Unit of a medium-sized public hospital in Goiás-Brazil. For each case, two controls were selected. Data on socioeconomic, clinical, and hospital costs were collected. To verify associations between variables, Odds Ratio and linear regression were calculated. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In the study of Osme et al (2021) with intensive care patients, it was stated that HCAIs prolong the length of stay in the hospital and place an extra burden on the health system (25). In the literature, examination of the economic dimension of HCAIs in the ICU is very limited, and existing studies have reached similar results to the present study (25,38). It is thought that the decrease in examination and treatment interventions in the present study, which was due to the decrease in infection rates and the shortening of the hospital stay, also caused a decrease in costs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the study of Osme et al (2021) with intensive care patients, it was stated that HCAIs prolong the length of stay in the hospital and place an extra burden on the health system (25). In the literature, examination of the economic dimension of HCAIs in the ICU is very limited, and existing studies have reached similar results to the present study (25,38). It is thought that the decrease in examination and treatment interventions in the present study, which was due to the decrease in infection rates and the shortening of the hospital stay, also caused a decrease in costs.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, the length of hospital stay is an important criterion used to evaluate the financial burden of HCAIs (37). In the study conducted by Leal and Freitas-Vilela (2021), it was concluded that the hospitalization cost of intensive care patients who developed was four times higher than the patients who did not develop infections, and that there was a relationship between infection and longer hospital stay (38). In the study of Osme et al (2021) with intensive care patients, it was stated that HCAIs prolong the length of stay in the hospital and place an extra burden on the health system (25).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was not consistent with that of the other studies. 47 , 51 , 52 Another review showed that all SSIs were not similar. Although by definition, all SSIs were costly; however, the principal determinants of the cost of an SSI were geographic locale, the type of surgery performed, and the depth of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…second most common healthcare-associated infection (HAI), accounting for 27% of all HAIs. [9][10][11] The mortality rate associated with VAP in Brazil is estimated to be around 30%-50%. 12 13 Given the high incidence and mortality rate of VAP, there is a need for reliable surveillance methods to accurately identify and track cases.…”
Section: Open Accessmentioning
confidence: 99%
“…In Brazil, VAP is also a significant public health problem, with a reported incidence ranging from 10 to 57 cases per 1000 ventilator days 8. A study conducted in a tertiary hospital in Brazil found that VAP was the second most common healthcare-associated infection (HAI), accounting for 27% of all HAIs 9–11. The mortality rate associated with VAP in Brazil is estimated to be around 30%–50% 12 13…”
Section: Introductionmentioning
confidence: 99%